The concise Oxford companion to African American literature - Andrews, William L., 1946-; Foster, Frances Smith; Harris, Trudier (Oxford University Press, 2001)
Presents more than 400 biographies of authors, critics, literary characters, and historical figures, and 150 plot summaries of major works. Covers a range of writers from Sojourner Truth to Frederick Douglass, and Ralph Ellison to Toni Morrison. Contains entries on major works (including synopses of novels) and also incorporates information on literary characters, as well as on character types such as Aunt Jemima and Brer Rabbit. Looks at icons of black culture, including Muhammad Ali, John Coltrane, Marcus Garvey, Jackie Robinson, John Brown, and Harriet Tubman. Includes general articles on poetry, fiction, and drama and on autobiography, slave narratives, Sunday School literature, and oratory, as well as other related topics.